2013
DOI: 10.1016/j.addbeh.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The impact of elevated posttraumatic stress on the efficacy of brief alcohol interventions for heavy drinking college students

Abstract: Brief alcohol interventions (BAIs) have been widely adopted for use with college students and are associated with significant reductions in drinking and problems. However, many students do not respond to these approaches and little is known about risk factors for poor response. The current study investigated one possible risk factor by examining the impact of posttraumatic stress (PTS) symptoms on BAI efficacy. This study presents pooled data from two randomized clinical trials © 2012 Elsevier Ltd. All rights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…One possibility is that depressed students are more likely to demonstrate these processes, which, in turn, serve to maintain such symptoms (i.e., high negative affect and fatigue). Counselor-administered interventions that can be tailored to also focus on coping skills and motives for drinking relevant to life stress and depressed mood might be most effi cacious in treating college students displaying such characteristics (e.g., Monahan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that depressed students are more likely to demonstrate these processes, which, in turn, serve to maintain such symptoms (i.e., high negative affect and fatigue). Counselor-administered interventions that can be tailored to also focus on coping skills and motives for drinking relevant to life stress and depressed mood might be most effi cacious in treating college students displaying such characteristics (e.g., Monahan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In 5 trials rated as low to moderate risk of bias in students (37,48,49,52), e-interventions resulted in no statistically significant reduction in binge drinking (MD, −0.1 episodes [CI, −0.6 to 0.4]) at 6-month follow-up. Effect sizes had moderate heterogeneity (Q = 8.8; P = 0.066; I 2 = 55%); 1 trial rated as low risk of bias that studied human support reported significant effects (44).…”
Section: Va Author Manuscriptmentioning
confidence: 99%
“…That is, counselor-delivered interventions may be particularly efficacious relative to computer-delivered interventions among individuals with riskier social networks. Efficacy of counselor- versus computer-delivered interventions varies as a function of individual differences at both short-term follow-ups (i.e., 1-3 months; Carey, Henson, Carey, & Maisto, 2009; Donohue et al, 2004; Mastroleo, Murphy, Colby, Monti, & Barnett, 2011) and longer-term follow-ups (i.e., beyond 3 months; Monahan et al, 2013). Social network attributes may therefore moderate intervention efficacy in the context of both initiation and maintenance of change.…”
mentioning
confidence: 99%